(untitled) (Medico Legal Update, 2020)
Hypertension is a major risk factor and antecedent of cardiovascular and end organ damage (myocardial infarction, chronic kidney disease, descriptive design was conducted in Babylon city outpatients and health centers to identify psycho-social burdens of patients with hypertension,A questionnaire including demographic information and tow validated instruments assessing psychosocial burdens of hypertensive patients,Data were collected through self-administration of questionnaire regarding the study,Data were analyzed through applying descriptive analysis as frequency, percentage, The participants had 43-48 years aged (45.1%) and were married (88.0%) with Not educated (52.2%) and (71.7%) were Male, the physical indicators of sample weight 90 and more kg (50%) and height was 151-160 cm (38.6%) with normal BMI (38.0%). Patients face stress and each day and the lack of enough time to relax and the lack of a holiday in the middle of the week, lead them to suffer various health problems such specially hypertension.